Acute renal failure in critically ill newborns increases the risk of death: a prospective observational study from India. (1st September 2016) - Patel, Ankur; Sharma, Deepak; Shastri, Sweta; Sharma, Pradeep
Abstract: Objective : To determine the incidence and risk factors of acute renal failure (ARF) in hospitalized critically ill neonates and analyze outcome of all neonates with renal failure in relation to risk factors. Material & methods : In this prospective observational study 815 infants were enrolled. Renal profile (blood urea and serum creatinine) was done after 12 h of life (or at the time of admission for outborn babies) and then every 12 hourly. Daily 24 h urine output was evaluated. Results : Incidence of renal failure in critically ill neonates was 10.67%. Out of 87 ARF neonates 52 (60%) expired. Mortality in the renal failure group was significantly higher in comparison to control group ( p  < 0.01). Non-oliguric renal failure was more common than oliguric renal failure, but mortality in the oliguric renal failure group was more. Neonatal sepsis was the most common cause of ARF. Eight neonates underwent peritoneal dialysis (PD) out of which there were seven neonatal deaths. Conclusion : Prognosis of neonates with ARF requiring PD was very poor. It can thus be concluded that the health care personal should do rapid diagnosis of ARF in neonates with potential risk factors and also goal at an early and effective treatment of these risk factors in neonates with ARF.